An investigation into the possible neuroprotective properties of phenytoin - Naga, Nishal (Rhodes University, Faculty of Pharmacy, Pharmacy, 2002)
Cerebral ischaemia, traumatic injury to the brain, inflammatory neurological disorders and HIV infections are amongst the most prevalent causes of neurodegeneration. Neuroprotective strategies are usually to limit the progressive secondary injury that generally occurs, thus limiting overall tissue damage. Neuroprotective strategies are usually to limit the progressive secondary injury that generally occurs, thus limiting overall tissue damage. Sodium channel blockers have been often used for this matter as they prevent the cascade of events culminating in free radical generation and eventually neuronal apoptosis. Newer compounds, such as antiperoxidants and free radical scavengers, show encouraging experimental results, but their clinical use is still very limited. Phenytoin being a popular drug in the treatment of epilepsy has also been used as a neuroprotectant during certain neurological emergencies and in pharmacological prophylaxis of post-traumatic epilepsy. Furthermore this agent functions by prolonging inactivation of voltage gated sodium channels. In these sets of experiment the neuroprotective properties of phenytoin were examined. The histological study revealed that phenytoin confers protection to the CA1 and CA3 regions of the hippocampus under the insult of QUIN. Cells maintain their characteristic shape and minimal tissue necrosis occurs in the presence of this agent. The in vitro effect of this antiepileptic drug on free radicals generation shows that phenytoin does not reduce or prevent the formation of these reactive species. Lipid peroxidation was induced using QUIN and iron (II), two known neurotoxins. The study reveals that only lipid peroxidation induced using iron (II) is reduced by phenytoin. These experiments were carried out in whole rat brain homogenate. These studies show that phenytoin possesses poor free radical scavenging properties. However, the dose-related reduction of iron-induced lipid peroxidation allows for speculation that phenytoin interacts with iron in order to reduce neuronal damage. Metal binding studies were performed using UV, IR and electrochemical analysis to examine the interaction of phenytoin with iron (II) and iron (III). Phenytoin, when added to iron (II) in solution, first oxidises the latter to iron (III) and maintains it in that form. A shift in the peak was observed in the UV spectrum when iron was added to phenytoin. Moreover, electrochemical studies indicate that the interaction between the metal and the ligand is very weak. The IR analysis it shows that phenytoin may be coordinating with iron through the Nitrogen atom on the phenytoin molecule. These studies show that phenytoin maintains iron in its oxidised form, which is a good property to possess as a neuroprotectants. Pineal organ culture showed that phenytoin does not increase melatonin production but slightly and non-significantly reduces the levels of this pineal hormone. However there is a significant rise in precursor NAS levels. As melatonin is known to possess antioxidant and free radical scavenging properties, this could mean that this drug can cause the CNS to become more susceptible to attacks by reactive oxygen species.
Keywords: Phenytoin -- Therapeutic use; Phenytoin -- Physiological effect; Nervous system -- Degeneration -- Prevention